Evidence of strong small-scale population structure in the Antarctic freshwater copepod Boeckella poppei in lakes on Signy Island, South Orkney Islands - Maturana, Claudia S.; Segovia, Nicolas; Gonzalez-Wevar, Claudio A.; Diaz, Angie; Rosenfeld, Sebastian; Poulin, Elie; Jackson, Jennifer A.; Convey, Peter (My University, 2020)
Environmental conditions were particularly severe during the Last Glacial Maximum, altering the distribution of the Southern Hemisphere biota, particularly at higher latitudes. The copepodBoeckella poppeiis the only macroscopic continental invertebrate species known to be distributed today across the three main biogeographic regions in Antarctica as well as in southern South America. Signy Island (South Orkney Islands) is a unique location for the study of Antarctic freshwater ecosystems due to its location and geographic isolation; it contains 17 lakes in several low altitude catchments. We conducted phylogeographic and demographic analyses using thecox1 gene on 84 individuals ofB. poppeifrom seven lakes across Signy Island. We recorded low levels of genetic diversity and a strong genetic differentiation signal between the eastern and western valleys within the island. Phylogeographic structure and demographic inference analyses suggested at least one asymmetrical dispersal event from west to east. Demographic inference detected a strong signal of population growth during the deglaciation process, which may have followed either (1) a strong genetic bottleneck due to a reduction in population size during the last glacial period, or (2) a founder effect associated with postglacial recolonization of Signy Island from elsewhere. The genetic architecture of this island's populations ofB. poppeishows that historical events, rather than continuous dispersal events, likely played a major role in the species' current distribution. Finally, our study considers possible mechanisms for dispersal and colonization success of the most dominant species in the Antarctic freshwater community.
Keywords: Population bottleneck; Biota; Last Glacial Maximum